Evaluation of the Maricopa County (Arizona) Demand Reduction Program, 1989-1991 - Hepburn, John R. ([Verlag nicht ermittelbar], 1994)
These data were collected to evaluate the Demand Reduction Program, a program initiated in Maricopa County, Arizona, in 1989 to combat drug abuse. A consortium of municipal, county, state, and federal law enforcement agencies developed the program, which stressed user accountability. The Demand Reduction Program had two objectives: (1) to create community-wide awareness of the severity of the drug problem and to alert drug users to the increased risk of legal sanctions, and (2) to adopt a zero-tolerance position of user accountability through an emphasis on increased and coordinated law enforcement activities directed against individual offenders and special treatment programs in lieu of prosecution. Part 1 of the collection, Demand Reduction Program Data, provides information on prosecutor's disposition, arrest date, submitted charges, filed charges, prior charges, disposition of charges, drugs offender used in last three months, information on prior drug treatment, type of attorney, and arrestee's age at arrest, sex, marital status, income, and living arrangement. Part 2 is a Citizen Survey conducted in January 1990, ten months after the implementation of the Demand Reduction Program. Adult residents of Maricopa County were asked in telephone interviews about their attitudes toward drug use, tax support for drug treatment, education, and punishment, their knowledge of the Demand Reduction Program, and demographic information. Parts 3 and 4 supply data from surveys of Maricopa County police officers, conducted in March 1990 and April 1991, to measure attitudes regarding the Demand Reduction Program with respect to (1) police effort, (2) inter-agency cooperation, (3) the harm involved in drug use, and (4) support for diversion to treatment. The two police surveys contained identically-worded questions, with only a small number of different questions asked the second year. Variables include officer's rank, years at rank, years in department, shift worked, age, sex, ethnicity, education, marital status, if officer was the primary or secondary wage earner, officer's perception of and training for the Demand Reduction Program, and personal attitudes toward drug use. Part 5 provides arrest data from the Maricopa County Task Force, which arrested drug users through two methods: (1) sweeps of public and semi-public places, and (2) "reversals," where drug sellers were arrested and replaced by police officers posing as drug sellers, who then arrested the drug buyers. Task Force data include arrest date, operation number, operation beginning and ending date, operation type, region where operation was conducted, charge resulting from arrest, Demand Reduction Program identification number, and arrestee's sex, race, and date of birth.